2012
DOI: 10.1007/s10551-012-1250-5
|View full text |Cite|
|
Sign up to set email alerts
|

The Limits of Corporate Social Responsibility: Techniques of Neutralization, Stakeholder Management and Political CSR

Abstract: Since scholarly interest in corporate social responsibility (CSR) has primarily focused on the synergies between social and economic performance, our understanding of how (and the conditions under which) companies use CSR to produce policy outcomes that work against public welfare has remained comparatively under-developed. In particular, little is known about how corporate decision-makers privately reconcile the conflicts between public and private interests, even though this is likely to be relevant to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(254 citation statements)
references
References 73 publications
8
226
0
20
Order By: Relevance
“…The manipulation strategy also bears a close resemblance to Fooks et al's (2013) (Polishchuk, 2009;Vallentin and Murillo, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The manipulation strategy also bears a close resemblance to Fooks et al's (2013) (Polishchuk, 2009;Vallentin and Murillo, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in effect, companies are not implementing community initiatives simply for ethical or philanthropic reasons but for more instrumental reasons such as long-term profit maximisation (Navarro, 1988) through the creation of competitive and comparative advantages for the firm (Hillman and Keim, 2001;Porter and Kramer, 2002;Waddock and Boyle, 1995) and in order to gain socio-political legitimacy (Hemphill, 1999) from powerful institutional stakeholders. Although previous studies have examined the potential instrumental benefits of corporate community initiatives (Fooks et al, 2013;Saiia et al, 2003), very few studies (but see Zhao, 2012) investigate how companies exploit these initiatives to seek legitimacy from the state and other key institutional actors. Some studies, such as the one conducted by Su and He (2010), have shown that firms engage in philanthropy to maximise the firm's benefits, not in the form of an immediate economic return, but rather in order to maximise their 'political return', which is designed to circumvent regulation or seek to be better protected from government intervention or legislation.…”
Section: Corporate Social Responsibility: Discretionary Strategic Ormentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a small body of research emerged in the 1980s to develop the concept of techniques of neutralization to corporate wrongdoing: the illegitimate activities that corporation engages in [12,13,14]. More recently there has been a resurgence of research that has applied this basic approach to corporate wrongdoing ( [15,16,17]; and [18]). This work uses precisely the same framework set out by Sykes and Matza and followed by Cohen (though remarkably, Cohen refers to none of this work on corporate denial in his work on state denial; 1993 and 2001).…”
Section: Corporate Techniques Of Neutralizationmentioning
confidence: 99%